EFFECTIVENESS OF MOBILE PHONE USERS BASED ON AGING ISSUE: IN THE CONTEXT OF URBAN PART OF CHINA - Law, Kian Aun (International Journal of Psychosocial Rehabilitation, 2020)
This paper can be on the basis of the description of the general statistics, using clustering and spatial statistics and grey model to deeply demonstrate the data owing to its particularity od data. It can provide new thoughts, new perspectives, new methods and new paths for related elderly research by analyzing generality and individual characters of the behavioral activities of the elder cell phone users. Based on the literature research on the aging of population and the research status of the elderly, the interaction between the elderly and TV media, the interaction between the elderly and mobile media and other aspects, this paper explains the problems related to the consumption behavior of the elder mobile phone users. Taking the mobile phone user database of telecom operators as the original data, this paper makes a descriptive statistical analysis of the elderly's mobile phone consumption behavior, utilizing the spatial statistical analysis method grey model, and reveals the influencing factors and development trend of the elderly's mobile phone consumption behavior. In addition, combining the above research results, this paper points out the existing problems and potential business opportunities in the elderly mobile phone consumption market by analyzing the interviews with experts and marketing strategies of operators. Through the above research, this paper fills in the gap in the research on the behavior of elderly consumer groups in China, and shows the changes and influences brought by the aging society from a new perspective, providing new perspectives, research methods and research ideas for future research on the elderly.